Hybrid anchor system to eliminate end peeling of flexurally strengthened reinforced concrete beam - Alam M.A.; Amin M.T.E.; Jumaat M.Z.; Muda Z.C. (Indian Society for Education and Environment, 2023)
The main aim of this article is to review the existing anchor systems and to propose new technique of end anchor to eliminate premature end peeling of plate bonded flexurally strengthened reinforced concrete beam. The proposed hybrid anchor system consists of connector and anchor plate. The connector and anchor plate of hybrid anchor system would resist the interfacial shear stress and normal stress respectively, thus, it could prevent the premature end peeling and reduce the size of the anchor plate significantly.